2020
DOI: 10.3389/fped.2019.00566
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Health-Related Quality of Life and HbA1c Values of Children and Adolescents With Diabetes Mellitus Type 1 Over 6 Months: A Longitudinal Observational Study

Abstract: Introduction: To achieve optimized blood glucose concentrations (assessed by HbA1c) and high health-related quality of life (HRQL), children and adolescents with diabetes mellitus type 1 (T1DM) must follow strict disease management strategies. This study aims to investigate HRQL of children and adolescents with T1DM and its association with HbA1c values over the course of 6 months. Methods: Patients aged 7-17 years (n = 203) with T1DM provided HRQL data on a monthly basis. HRQL was measured using the Kids-CAT,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…In this 6‐month intervention, no difference was found in the two adult cohorts 18 . In contrast, a German study observed lower scores in some domains of the HRQOL instrument Kids‐CAT in children and youths with HbA1c > 9% 19 . However, it is possible that our questionnaires on HRQOL did not cover specific aspects that can be influenced by monthly video consultation, such as an increased feeling of security or control through more frequent contacts with the diabetes team.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In this 6‐month intervention, no difference was found in the two adult cohorts 18 . In contrast, a German study observed lower scores in some domains of the HRQOL instrument Kids‐CAT in children and youths with HbA1c > 9% 19 . However, it is possible that our questionnaires on HRQOL did not cover specific aspects that can be influenced by monthly video consultation, such as an increased feeling of security or control through more frequent contacts with the diabetes team.…”
Section: Discussionmentioning
confidence: 70%
“…18 In contrast, a German study observed lower scores in some domains of the HRQOL instrument Kids-CAT in children and youths with HbA1c > 9%. 19 However, it is possible that our questionnaires on HRQOL did not cover specific aspects that can be influenced by monthly video consultation, such as an increased feeling of security or control through more frequent contacts with the diabetes team. Nevertheless, the treatment-specific outcomes, namely, diabetes burden and treatment satisfaction, differed FDR significantly between IG and WG in our study.…”
Section: Extension Phase: Analysis Of Metabolic Control Hba1cmentioning
confidence: 99%
“…Overall, the quantitative evaluation demonstrated that our sample of adolescents had similar characteristics in terms of gender, insulin pump use, and average A1c levels compared to US registries and European studies. 50 , 51 The subgroup of adolescents who had low WHO‐5 scores, underwent secondary screening, and received a timely assessment by a child psychiatrist allowing access to follow‐up care without the need for a referral to community mental health services. The timely assessments were facilitated by additional funding to support the TeleLink Mental health Program.…”
Section: Discussionmentioning
confidence: 99%
“…16 Psychosocially, associating positively with peers is important and seems to influence the decision-making process in selfmanagement, distress, negative moods, and negative self-image/confidence-all of which are factors that affect poor glycemic control. 11,17,18 One quantitative study revealed how the age group of emerging adults (18)(19)(20)(21)(22)(23)(24)(25) rated themselves as having the lowest Health-Related Quality of Life (HRQOL) compared to other age groups. 19 This was confirmed by Fischer et al 20 who looked at adolescents and young adults aged 7-27, showing how increasing age is a significant determinant of low rates of HRQOL and low ratings of HRQOL correlated with poorly regulated blood glucose.…”
Section: Introductionmentioning
confidence: 99%
“…11,17,18 One quantitative study revealed how the age group of emerging adults (18)(19)(20)(21)(22)(23)(24)(25) rated themselves as having the lowest Health-Related Quality of Life (HRQOL) compared to other age groups. 19 This was confirmed by Fischer et al 20 who looked at adolescents and young adults aged 7-27, showing how increasing age is a significant determinant of low rates of HRQOL and low ratings of HRQOL correlated with poorly regulated blood glucose. In contrast, a study by Laffel et al 21 showed how the quality of life among children and adolescents with diabetes aged 7-17 is the same as that among controls; however, discrepancies in HRQOL were seen in reports of diabetes-specific family conflict.…”
Section: Introductionmentioning
confidence: 99%